Thermal behaviour and kinetic study of the olive oil production chain residues and their mixtures during co-combustion. (August 2016) - Buratti, C.; Mousavi, S.; Barbanera, M.; Lascaro, E.; Cotana, F.; Bufacchi, M.
Highlights: Co-combustion behaviour of PR with 2PH and 3PH was studied. Effects of blending ratio and heating rate on the combustion process were analysed. A synergistic effect was observed in PR-2PH and PR-3PH blends. Reactivity of the blends increase with increasing PR. The minimum apparent activation energy was obtained for 25PR752PH mixture. Abstract: The kinetic behaviour of olive tree pruning (PR), two- (2PH) and three-phase (3PH) olive pomace and their blends was investigated under combustion condition using thermogravimetric analysis. PR was blended with 2PH and 3PH at different ratios (25:75, 50:50 and 75:25) and tested in the temperature range from ambient to 1000 °C in order to evaluate the co-combustion behaviour. Results showed that the thermal degradation of all samples can be divided into three regions (drying, devolatilisation, char oxidation) with different combustion properties, depending on the percentage of PR. Significant interaction was detected between the fuels, and reactivity of 2PH and 3PH was improved upon blending with PR. The iso-conversional methods, Ozawa–Flynn–Wall and Vyazovkin, were employed for the kinetic analysis of the oxidation process. The results revealed that the activation energy of PR was higher than the one of 2PH and 3PH, and the minimum value was obtained for 25PR752PH sample.